Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species - Hosseininaveh, Fatemeh; Nozari, Jamasb; Kaydan, Mehmet Bora; Hosseininaveh, Vahid (Zootaxa, 2016)
Members of the family Diaspididae (Hemiptera: Coccomorpha) can be devastating pests that suck parenchyma cell contents from crops and cause severe damage to pistachio trees (Pistacia vera L.). The current research collected and characterized diaspidid species from pistachio orchards in Kerman province, Iran, according to their morphological and molecular features. Lepidosaphes pistaciae Archangelskaya, Suturaspis davatchi (Balachowsky & Kaussari) and Melanaspis inopinata (Leonardi) are redescribed and a new species, Melanaspis pistaciae Hosseininaveh & Kaydan sp. n., is described. Phylogenetic trees based on molecular analysis of COI and 28S rDNA fragments placed all the species in separated clades and confirmed M. pistaciae as a new taxon which is concluded by morphological differences. Molecular analysis suggests non-monophyly of the populations of each species. Melanaspis pistaciae sp. n. has spread to most cultivated pistachio areas in Iran and has probably been misidentified as M. inopinata in the past. Further investigation of the biology of this species may lead to development of more effective approaches for controlling this pest.